Lateral rectus palsy following coronary angiography and percutaneous coronary intervention. (17th February 2014) - Nicholson, Luke; Jones, Ruth; Hughes, David S
Abstract : We present a rare case of unilateral lateral rectus palsy following an elective coronary angiography and percutaneous coronary intervention in a 78-year-oldwoman. Ophthalmoplegia following coronary angiography is extremely rare and this is the first case of a unilateral lateral rectus palsy following the procedure.